25.2: Effect of Screen Reflectivity on Color Gamut in projection system. (24th February 2021) - Wang, Guan; Yang, Yuhua; Yao, Binghui; Gu, Chun; Xu, Lixin
Abstract : Compared with the planar color gamut, the stereoscopic color gamut is more uniform, it can reflect the actual situation of the color gamut of the display system by considering the changes in the brightness. In this article we introduce another advantage of using stereoscopic color gamut, it can reflect the external factors of the display system, such as the influence of the spectral reflectivity of the screen. When the color space is converted from CIEXYZ to CIELAB, we use a fixed white point, these results are more intuitive and reasonable.